Adapting roughages varying in quality and curing processes to the nutrition of beef cattle. Comparative value of four varieties of forage sorghum silage for wintering weaned beef calves. - Smith, E.F.; Richardson, D.; Cox, R.F.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
The production of sorghum silage in Kansas has, during the past 20 years, grown from an insignificant source of farm income to one of major proportions. The total value of sorghums produced for silage and forage is about $40 million. Each year silage accounts for about two thirds of this total, or about $26 million. As more acres are retired from production of price-support crops, sorghum acreage is expected to increase still more.
Keywords: Beef; Roughages; Sorghum silage